Analysis Online Games on Students' Learning Motivation In Upper Grades Elementary School - Nugroho, Muhammad Taufik (Nur Science Institute, 2024)
Background: This study aims to: 1) describe the factors of online games on the motivation of students studying at SD IT Nur Hidayah Surakarta; 2) describe the right and appropriate efforts in anticipating the decrease in student motivation; 3) describe the types of online games played by upper class students 4) describe the impact received from playing online games on student motivation. Method: This type of research used in this research is descriptive qualitative research that describes the characteristics or characteristics of individuals, circumstances, symptoms or certain groups. Data collection techniques by interview, observation, and documentation. Research sources are students, teachers and principals. Technical analysis of data uses an Interactive analysis model. While the validity of the data uses triangulation of sources and techniques. Result: The results showed: 1). Factors that influence learning motivation, namely: There is a desire from within students to reach their desires such as being given gifts, rewards, monitoring children's activities from the environment around student learning 2). Efforts to improve student learning, namely: The existence of interesting and fun activities in learning, The existence of rewards in learning, Encouraging students to move in class, Creating competition and cooperation between students in learning, Providing comments and appreciation for student work 3). types of online games among elementary school students, namely: games of the type FPS, RPG and console 4). Impact of online games, namely: The positive impact of online games on learning motivation, the negative impact of online games on player health